De Sint-Servaaskerk te Maastricht in de vroege middeleeuwen - Titus A.S.M. Panhuysen (Bulletin KNOB, 1991)
Till recently only very concise sources revealed something on the previous collegiate, now parish church of St. Servatius' predecessors. Thus Gregorius of Tours (538/9-594/5) mentions a wooden tomb house on the site of the grave of Bishop Servatius (departed about 380) and, to Servatius' honour, the erection of a templum magnum by Bishop Monulf in the second half of the 6th century. During the 9th century the Gesta sanctorum patrum Fontanellensis coenobii describe a monastery 'beati Servatii', to which Abbot Wando from Saint-Wandrille has been exiled in 719. Although suspect 11th century sources mention Charles Martell's building activities in the same times (after 726) we are not informed on the accessory church.